Equine ulcerative keratitis with furrow: A review of the outcomes of 72 cases from 1987 to 2015. (5th April 2019) - Berkowski, W. M.; Craft, W. F.; Whitley, R. D.; Brooks, D. E.; Plummer, C. E.
Summary: Background: Ulcerative keratitis with peripheral furrow formation is a poorly‐described condition which has been associated with a grave prognosis due to rapid necrosis of the cornea. Objective: To describe the infectious aetiologies associated with furrow‐forming ulcerative keratitis, its overall clinical course and the efficacy of medical and surgical intervention in horses. Study design: Retrospective clinical case series. Methods: Medical records of 72 horses which presented with furrow‐forming ulcerative keratitis at the University of Florida between 1987 and 2015 were reviewed. Results: Seventy‐two horses (72 eyes) with furrow‐forming ulcerative keratitis were treated at the University of Florida between 1987 and 2015. Of these, a definitive aetiologic diagnosis was available for 37 eyes. Ten of 37 eyes (27%) were diagnosed with fungal keratitis based on cytology of corneal scraping, culture, histopathology and/or fungal PCR. Fourteen of 37 eyes (38%) were diagnosed with a mixed fungal and bacterial keratitis. Thirteen of 37 eyes (35%) were diagnosed with bacterial keratitis. Overall, 26 of 72 total eyes were treated with medical therapy alone (36%). Forty‐six of 72 eyes were treated medically and surgically (64%). Of the 26 eyes which received medical therapy, 20 healed with a positive visual outcome (77%) and 6 eyes were non‐visual (23%). Of the 46 eyes which received surgical intervention, 40 healed with a positive visual outcome (87%), while six eyes were non‐visual (13%). Altogether, 60 of 72 eyes healed with a positive visual outcome following medical or surgical treatment of furrow‐forming ulcerative keratitis (83%). Twelve of 72 eyes failed treatment (17%), with six eyes requiring enucleation and six globes becoming phthisical after treatment. Main limitations: Inconsistencies in available medical record data due to the large span of time (1987–2015) are inherent in this retrospective study, along with gradual evolution of corneal surgical techniques and medical therapies over the decades. Conclusions: Furrow‐forming ulcerative keratitis was associated with a positive visual outcome in 83% of horses treated at the University of Florida between the years 1987 and 2015. Furrow formation may be associated with either fungal or bacterial infection.